EFFECT OF INFRASTRUCTURE ON ECONOMIC GROWTH IN SOUTH SUMATERA PROVINCE - Kale Kaupa (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2015)
The aim of this paper is to study the effect of water supply infrastructure and electricity infrastructure which are considered as public utilities and road infrastructure which is considered as public works on economic growth in South Sumatera. I further extend the analysis to include the impact of infrastructure on three key sectors: agriculture sector, manufacturing sector and trade sector. In this paper, I use time series data from year 2001 to 2013. I measure economic growth as per capita GRDP. The approach is based on the growth model of Barro (1990). Infrastructure capital is an input into aggregate production. Using physical infrastructure as independent variables and employing Cobb-Douglas production function in the framework of Barro’s growth model, the result provides clear evidence that electricity infrastructure and water supply infrastructure are significant and both positively affect per capita output in the province. This is also true in the agriculture sector, manufacturing sector and the trade sector. On the other hand, road infrastructure doesn’t not show any significant impact. Overall, the results are consistent with the widely-accepted idea in policy research that infrastructure plays an important role in promoting growth, as well as with the viewpoint that certain conditions of the local economy may hinder the growth-related impacts of existing infrastructure.